STRATEGI GURU DALAM MENGONSTRUKSIKAN KONDISI PEMBELAJARAN - - Sukardi Ks (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2015)
A teacher has big responsibilities when he/she does his/her work. The duty of a teacher is not only to teach in the classroom but also to become a model who motivates, facilitates, constructs, and inspires his/her students. One the principles of professionalism is to have a competence requiredaccording to the competence standard. The competence of a teacher can be understood as a combination of knowledge, skills, anad behavior manifested in any smart and responsible action he or she does in doing the duty as a learning agent. The competences of a teacher as a learning age nt as stated in UUGD No. 14 Year of 2015, is paedagogic, personality, social, and professional competences. A good teacher is someone who can inspire the students as well as is liked by them. Inorder to make a teacher can inspire the students, his or her behavior has to be a role model for the students. To make a teacher can do the duty professionally, he or she has to be able to construct an active, innovative, creative, effective, and enjoyable learning. Besides, a teacher has to have a good character, is able to conduct researches, and can act smartly. Keywords: teacher, professional, to construct learning